Mindfully Reframing the Psychological Impact of the COVID-19 Outbreak Through a Social Media Community for Students: A Pragmatic Study - Pagnini, Francesco; Bonalda, Elisa; Montrasi, Eleonora; Toselli, Elena; Antonietti, Alessandro (Frontiers in Psychology, 2021)
The COVID-19 outbreak and the restrictions that have been enforced by the health authorities are having a profound psychological impact on the population. Many people, including the students, faced forced modifications to their daily lives and this prompted the need for scalable strategies to promote resilience. We designed an online community intervention for psychology students and recent alumni aimed to promote functional coping strategies through openness and cognitive flexibility. This psycho-educational intervention was delivered through a private group on social media (Facebook) during the acute phase of the lockdown period and it involved the publication of exercises and quick lectures. Contents were posted regularly and members of the community were invited to share their comments. The posts included stimuli that promote open and flexible reflections on the current situation. The overall aim of this group was a cognitive reframing on the epidemic effects, promoting creative and flexible thinking. We ran a thematic analysis of the interactions and we collected qualitative feedback at the end of the intervention. The participants’ comments dealt with changes in their perspectives, sharing discomfort, encouragement and support, and building a sense of community. Post-intervention comments were highly satisfied and confirmed the helpfulness of the intervention to promote flexibility and openness, eventually helping to manage the negative emotions related to the COVID-19 outbreak. This study provides preliminary evidence that an online psycho-educational community stimulating flexibility and openness can help to reframe the negative psychological impact of the outbreak, improving their management.